FRI0359 Intravenous cyclophosphamide combined therapy in severe lupus nephritis: Immediate and long-term results. (23rd January 2014) - Vachvanichsanong, P.; Dissaneewate, P.; McNeil, E.
Abstract : Background: Intravenous cyclophosphamide (IVCY) has been used to treat severe lupus nephritis (LN) for many years. Because of the wide variety of manifestations of the condition and the long-term nature of the disease, outcomes vary widely. Objectives: To evaluate and compare the immediate and long-term results of IVCY in pediatric onset severe LN and between patients with normal and abnormal renal function. Patients and Methods: The records of patients aged <18 years who attended the Department of Pediatrics, Prince of Songkla University, diagnosed with severe LN, and who were given a 36-month IVCY course, were reviewed. Results: 108 patients were studied with a mean age of 12.6±2.7 years and mean follow up time of 5.7±4.3 years. 48 patients completed the 36-month IVCY course, 29 did not complete the course, and 31 were ongoing at the time of analysis. There were 36 patients with abnormal renal function at the start of therapy and 72 with normal renal function. Abnormal renal function patients had a higher mortality rate than normal renal function patients (13/36 vs 10/72, p-value<0.001). Both groups responded well initially to treatment; proteinuria reduced to normal levels after 1 and 2 courses in the normal and abnormal renal function groups, respectively, while creatinine clearance returned to normal levels after 8 courses in patients with abnormal renal function. Conclusions: Three years of IVCY treatment reduced proteinuria in both normal and abnormal renal function patients; however the mortality rate was higher in patients with abnormal renal function. Disclosure of Interest: None Declared